Evolution of allometric changes in fruit fly legs: a developmentally entrenched story (2016)
Allometric studies measure the scaling changes between different body parts and these often have implications on understanding ecology and evolution. Although most work on allometry has described its importance during phenotypic evolution, few studies have focused on studying how entrenched developmental processes can affect allometric changes. To explore this problem, here we used the sex comb, a male-specific group of bristles with a spectacular morphological diversity among Drosophila species. By combining morphometric analysis in wild type and genetically perturbed D. melanogaster and Drosophila species, we studied the allometric changes that occur in leg length and other bristle rows in concert with sex comb radiation. We show that bristle-developmental processes are important for understanding the allometric changes of Drosophila first tarsal segments. Different lines of evidence suggest that a complicated interaction between bristle spacing and movement are crucial for understanding the evolution of allometry in this system. As a result, this work shows that although the emergence of a new trait, the sex comb, can modify the allometric relationships, there is a hierarchy of ancestral developmental processes with respect to how easily they can be modified. As a result, the interconnection of developmental processes can bias the direction of morphological changes.